2007
DOI: 10.1016/j.jim.2007.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hepatitis E-specific cell-mediated immune response using IFN-γ ELISPOT assay

Abstract: In developing countries, hepatitis E (HEV) and hepatitis A (HAV) are the major causes of acute viral hepatitis with similar fecooral modes of transmission. In contrast to the high seroprevalence of hepatitis A infection, a low seroprevalence of HEV among children in endemic areas has been reported. These data suggest the possibility that silent HEV infection is undiagnosed by the current available methods. Many of the serological tests used for HEV diagnosis have poor specificity and are unable to differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 59 publications
3
29
0
Order By: Relevance
“…6 cells. The authors suggested that the robust IgG antibody and cell-mediated responses detected in one well-studied U.S. patient who had traveled to Egypt 2 months prior to the study were likely due to (re)exposure in adulthood rather than to persistent cellular immunity from childhood (249).…”
Section: Protective Immunity Following Vaccinationmentioning
confidence: 99%
“…6 cells. The authors suggested that the robust IgG antibody and cell-mediated responses detected in one well-studied U.S. patient who had traveled to Egypt 2 months prior to the study were likely due to (re)exposure in adulthood rather than to persistent cellular immunity from childhood (249).…”
Section: Protective Immunity Following Vaccinationmentioning
confidence: 99%
“…Thus, in agreement with a prior study [17], these longer peptides preferentially stimulated CD4 ϩ T cells. The secretion of interferon-␥ (IFN-␥) was detected by ELISPOT assays [18] Cultured lymphocytes were added at 5 ϫ 10 4 cells/well in quadruplicate and stimulated with peptide pools or media containing identical DMSO concentration for 18 hours at 37ЊC. Phytohemagglutinin (PHA; Sigma, St. Louis, MO) at 5 g/ml was used as a positive control.…”
Section: Human Ifn-␥ Elispot Assaymentioning
confidence: 99%
“…Novel techniques, such as an HEV-specific interferon-gamma (IFN-γ) ELISPOT that measure HEV-specific cell-mediated immune responses are not yet suitable for routine use [76]. This assay might provide a better measure of prior HEV exposure than seroprevalence studies.…”
Section: Laboratory Diagnosismentioning
confidence: 99%